PENGARUH PERHATIAN ORANG TUA, KONSEP DIRI TERHADAP PRESTASI BELAJAR MATA PELAJARAN PRODUKTIF IPS TERPADU PADA SMP AL-WATHONIYAH DI KOTA BEKASI - Risma Elida; Eka Putri (Jurnal Ilmu Pendidikan Ahlussunnah, 2021)
ABSTRAC This research aims to analyze (1) Parents' attention to students' self-concepts (2) Parents' attention to learning achievement (3) Self-concept towards learning achievement. This research is quantitative associative. The population of this research is Al-Watoiniyah Junior High School in Bekasi city which is registered in the 2019/2020 academic year, totaling 75 students, then a sample of 30 students is taken, this sampling uses data analysis techniques using testspath hypothesis and hypothesis testers.The results of the research conducted: (1) Significant parental attention to the self-concept of Al-Wathoniyah Junior High School students in the city of Bekasi in Integrated Social Studies subjects (2) Significant parental attention to learning achievement in the city of Bekasi in integrated Social Studies subjects (3) Concept influential selfsignificant effect on learning achievement in Integrated Social Studies subjects.Key: Parental Attention, Self-Concept, Learning Achievement Keywords: Parental Attention, Self-Concept, Learning Achievement